The Study of Jurisprudential Principles of Prohibiting Illegal Commercial Competition - Aref Hamdollahi; Asef Hamdollahi (مطالعات فقه اسلامی و مبانی حقوق, 2024)
If commercial enterprises resort to illegitimate actions or procedures in their relations with each other in order to attract commercial rivals’ customers, such actions are considered illegitimate competition; In addition to the legal prohibition, this type of competition also entails religious prohibition. The prohibition of illegitimate competition is considered one of the important issues of commercial law, and it seems necessary to examine its jurisprudential foundations in order to encourage businessmen to compete legitimately and to deter them from illegitimate competition in order to prevent losses and damages to individuals in business relationships. The present paper, in a descriptive and analytical way, aims to explain the jurisprudential foundations of the prohibition of illegal competition, by insisting on the rules such as “negation of harm” and “prohibition of obtaining property by illegitimate means” in order to limit by the first rule the right of businessmen to compete in order to prevent losses caused by illegal competition and apply the latter as a general rule in all financial fields, including commercial competition, and it intends to regulate the prohibition of illegal competition by resorting to the above mentioned rules, and also due to the sanctity of acquisition through illegitimate and haram means and acts, introduce illegitimate competition as one of the examples of forbidden incomes.